Sintesis Selulosa Suksinat Melalui Reaksi Esterifikasi Asam Suksinat - Miftahul Jannah; Ahyar Ahmad; Paulina Taba; Harningsih Karim (Jurnal Kimia Fullerene, 2023)
Cellulose is a biopolymer that is widely applied in various fields. Modification of cellulose is needed to increase the added value of cellulose. One of these cellulose derivatives is cellulose succinate. This study aims to synthesize succinic cellulose using succinic acid. This research covers the synthesis of cellulose succinate via esterification reaction with a variation of succinic acid (1.6%; 2.4%; 3.2% and 4.0%), DS determination by titration method, and characterization with FTIR. Based on the synthesis results, the optimum DS was obtained at 2.4% succinic acid (SS3) concentration, namely 0.692. The results of the characterization with FTIR also showed the presence of a C=O absorption band indicating the presence of cellulose succinate monoester.